Calibration Curve Building and Sensing Characteristics of Low Power Consumption H2 Gas Sensor - Nguyen, Van Toan; Nguyen, Xuan Thai; Nguyen, Van Duy; Chu, Manh Hung (JST: Engineering And Technology For Sustainable Development, 2021)
Detection and alarm of leakage of hydrogen (H2) gas is an extremely important issue needed to be addressed. In this study, we fabricated and calibation portable devices based on the H2 sensor using SnO2 thin film with Pd nanoscale catalytic as a sensing layer. For practical application of the sensor, we designed and realized PCB circuit boards, microprocessors, data processing, output signals, data storage, power sources and source code. This sensor based portable devices were able to monitor to as low as 25 ppm H2 gas. Power consumption and selectivity of the sensor were also investigated. This study will open another simple and low-cost approach to monitor toxic and flammable gases for environmental monitoring.